2018
DOI: 10.1175/bams-d-17-0014.1
|View full text |Cite
|
Sign up to set email alerts
|

BATAL: The Balloon Measurement Campaigns of the Asian Tropopause Aerosol Layer

Abstract: We describe and show results from a series of field campaigns that used balloonborne instruments launched from India and Saudi Arabia during the summers 2014–17 to study the nature, formation, and impacts of the Asian Tropopause Aerosol Layer (ATAL). The campaign goals were to i) characterize the optical, physical, and chemical properties of the ATAL; ii) assess its impacts on water vapor and ozone; and iii) understand the role of convection in its formation. To address these objectives, we launched 68 balloon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 33 publications
8
106
0
Order By: Relevance
“…Sulfate thus may not be the main contributor to the deficit in backscatter. Recent balloon‐based in situ observations of ATAL composition (Vernier et al, ) and data from the StratoClim airborne campaign (Höpfner et al, ) also suggest that sulfate may not be as important a component of the ATAL as previously assumed. The most likely explanation for this deficiency is that convective transport in the model, especially in the ATAL region, is too weak.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Sulfate thus may not be the main contributor to the deficit in backscatter. Recent balloon‐based in situ observations of ATAL composition (Vernier et al, ) and data from the StratoClim airborne campaign (Höpfner et al, ) also suggest that sulfate may not be as important a component of the ATAL as previously assumed. The most likely explanation for this deficiency is that convective transport in the model, especially in the ATAL region, is too weak.…”
Section: Discussionmentioning
confidence: 96%
“…A threshold of 5% in depolarization ratio is applied below 20 km to remove ice clouds. This simple cloud‐clearing approach results in a relatively good agreement (within 25%) between CALIOP and balloon‐borne in situ backscatter measurements from the Compact Optical Backscatter Aerosol Detector (COBALD) carried out from China (V15) and during the BATAL project in India and Saudi Arabia (Vernier et al, ). Enhanced SR, indicating the presence of aerosols, is found over an area extending between East Asia and North Africa, encompassing India and the Middle East.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Volcanic and smoke particles show rather different chemical, physical, and morphological properties. In contrast to liquid, spherical, less light-absorbing sulfuric acid droplets of volcanic origin, stratospheric smoke particles from the wildfires in 2017 were observed to be nonspherical Hu et al, 2019) and probably consisted of a solid core (black carbon (BC) aggregate) with nonspherical organic coating (Yu et al, 2019). In contrast to volcanic sulfuric acid particles, soot particles significantly absorb solar radiation (a direct effect on climate) and also influence the evolution of cirrus clouds by serving as INPs in heterogeneous ice nucleation processes (an indirect effect) (Hoose and Möhler, 2012;Kanji et al, 2017;Ullrich et al, 2017), unlike liquid sulfuric acid droplets which influence cirrus occurrence and evolution via homogeneous ice nucleation (Jensen and Toon, 1992;Sassen et al, 1995;Liu and Penner, 2002;Campbell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The aerosol optical thickness (AOT) in the UTLS region must have exceeded values of 2-3 at 500 nm wavelength so that strong absorption in the visible spectrum and warming of the smoke layers occurred and enabled the fire smoke plumes to ascend by about 2-3 km d −1 during the first days after injection, as was observed with the spaceborne lidar aboard CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation) (Khaykin et al, 2018). Peterson et al (2018) and Yu et al (2019) discussed the strength of this stratospheric smoke event based on spaceborne lidar observations and passive remote sensing and concluded that the pyroCb-driven aerosol injection into the UTLS was comparable with a moderate volcanic eruption, characterized by a volcanic explosivity index of 3-4. The 12 August 2017 event, denoted as the Pacific Northwest Event by Peterson et al (2018), injected 0.1-0.3 Tg of total aerosol particle mass into the lower stratosphere.…”
Section: Introductionmentioning
confidence: 99%